A STUDY TO ASSESS THE EFFECTIVENESS OF SODIUM BICARBONATE MOUTH WASH FOR PREVENTING RADIOTHERAPY INDUCED ORAL MUCOSITIS IN HEAD AND NECK CANCER PATIENTS IN SELECTED KLE CANCER HOSPITAL, AT BELGAVI” - Mr Prabhu,; Dr.Preeti Bhupali,; Dr. Honnagouda Patil, (The Bioscan, 2024)
A study is done to evaluate the Impact of Sodium bicarbonate of sodium bicarbonate mouth wash for preventing radiotherapy induced oral mucositis in head and neck cancer patients.Pre-test and post-test design for one group research design is used for the study. Total 82 head and neck cancer patients had selected with Purposive sampling technique. Socio demographic variables and Mucositis Assessment Scale is used for the data collection. Modified General System Theory is used for the study. The effect of study shows such the mean score of pretest was grade-3 was (24.4%) and grade-4 was (75.6%). Post-test grade- 3 was (64.6%), and (45.1%) on day grade-4, the assessment level at grade-4 on day grad-3 was (35.4%). Study proved that sodium bicarbonate mouth wash help to cure the OM of HNC patients.